Serum acid phosphatase activities in patients with lung cancer: a biochemical and immunohistochemical analysis of 25 cases. Issue 9 (September 1981) - Mortimer, G; Casey, M
Abstract : A series of 25 cases of lung cancer are presented in which total (TAcP) and nonprostatic serum acid phosphatase (NPAcP) activities were measured. Of these cases, 36% had raised TAcP and NPAcP activities in their serum. However, the serum activities of TAcP and NPAcP did not correlate with either the presence of lung cancer nor with the morphological tumour type. This fact indicates that, despite isolated reports of raised serum acid phosphatase activities in cases of lung cancer, acid phosphatase is of no value as a marker for lung cancer. We sought alternative explanations for the raised TAcP and NPAcP activities observed in our series in the hope that this enzyme might prove useful as a marker for early metastatic disease in lung cancer patients. This possibility is not substantiated, and the findings are analyzed and discussed. It is tentatively suggested that raised NPAcP activities in patients with lung cancer may relate to haemostasis.